Zirconia‐supported 11‐molybdovanadophosphoric acid catalysts: effect of the preparation method on their catalytic activity and selectivity. Issue 11 (18th October 2018) - Bakkali, Bouchra El; Trautwein, Guido; Alcañiz-Monge, Juan; Reinoso, Santiago
Abstract : The influence of the preparative method and thermal treatments on the performance of a model heterogeneous catalyst based on a zirconia‐supported heteropoly acid in the oxidation of adamantane with hydrogen peroxide is investigated in this work. Abstract : The oxidation of adamantane with hydrogen peroxide catalyzed by zirconia‐supported 11‐molybdovanadophosphoric acid is shown to be a suitable green route for the synthesis of adamantanol and adamantanone. This work evaluates how the catalyst activity and selectivity are affected by some of its preparative parameters, such as the method for supporting the catalytically active heteropoly acid over the zirconia matrix or the pretreatments applied to the resulting materials before being used as heterogeneous catalysts. Our results indicate that the most effective catalysts able to maintain their activity after several reaction runs are those prepared by following the sol‐gel route, whereas the most selective catalysts are those obtained by impregnation methods. Moreover, the calcination temperature has also been identified as a relevant parameter influencing the performance of catalysts based on supported heteropoly acids. The increasing catalytic activity observed over several consecutive reaction runs has been attributed to the formation of peroxo derivatives of polyoxometalate clusters at the surface of the catalyst and their accumulation after each reaction cycle.